Wiggsy Sivertsen and anti-rape demonstrators - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Wiggsy Sivertson with a group of women united against rape standing outside demonstrating. The women are holding a banner and a sign. The banner reads "[Wom]en's [C]enter" and the sign reads "Rape (with the universal symbol for no on the word), women united will never be defeated!". Wiggsy is standing in front of the banner and is looking at the camera.